New onset or exacerbation of psoriatic skin lesions in patients with definite rheumatoid arthritis receiving tumour necrosis factor α antagonists. Issue 3 (8th September 2005) - Kary, S; Worm, M; Audring, H; Huscher, D; Renelt, M; Sörensen, H; Ständer, E; Maaß, U; Lee, H; Sterry, W; Burmester, G-R
Abstract : Background: Blockage of tumour necrosis factor α (TNFα) is highly effective in rheumatic diseases, especially in rheumatoid arthritis (RA), ankylosing spondylitis, and psoriatic arthritis. Furthermore, TNFα antagonists have also been shown to significantly reduce psoriatic skin lesions. Case reports: A series of nine patients with RA who were treated with different types of TNFα antagonists and who unexpectedly developed either a new onset or an exacerbation of psoriatic skin lesions are reported